Desenvolvimento de matrizes poliméricas de alginato e pectina para o cultivo de células imobilizadas de Desmodesmus subspicatus em vinhaça de cana-de-açúcar - Jesus, Geise Cristina de (2018)
Among the main industrial wastewaters, sugarcane vinasse figures as an actual environmental concern, due to its polluting potential and large volumes available, about 10 liters per liter of ethanol. Considering the alternatives to vinasse disposal, fertirrigation is the most commonly used. However, it is currently being questioned due to its effects on the soil and on groundwaters, caused by nutrient lixiviation such as potassium. The application of immobilized microalgae for wastewater treatment with emphasis on the removal of nutrients has increased over the last years. The aim of this study was to develop uniform alginate and pectin beads for immobilization of Desmodesmus subspicatus and evaluate its growth and ability to carbon, nitrogen and potassium removal in vinasse. The process parameters of bead production, type and concentration of biopolymer (alginate 1, 2, and 3% w/v and pectin 5, 7 and 10% w/v) and crosslinking agent concentration (calcium chloride 2, 5 and 10% w/v), were varied in order to evaluate their influence on bead characteristics. Results indicated that stable alginate and pectin beads were produced and according to the preliminary particle characterization, concentrations of 2% alginate and 7% pectin were chosen for immobilization of D. subspicatus and growth in vinasse. Immobilized D. subspicatus showed cellular growth in vinasse, with maximum specific rates of 0.009 h-1 and 0.002 h-1 in alginate and pectin beads, respectively. In the tests performed with 2% alginate, the immobilized microalgae reached 42, 49 and 48% carbon; 34, 35 and 34% nitrogen and 22, 23 and 32% potassium removal; and for pectin 7%, the removals were 32, 39 and 41% for carbon; 11, 24 and 34% for nitrogen and 39, 36 and 35% for potassium, for 2, 5 and 10% of calcium chloride, respectively. The microalgae were able to grow and remove appreciable amounts of nutrients from the vinasse. Compared with the free microalgae cultivation, immobilized microalgae indicate good prospects for the use of nutrient removal from vinasse.